The effective factors on empowerment of faculty members to launch start-ups - Hesari , Zahra; Jahanian, Ramezan; Hosseini , Mohammadali (Social Determinants of Health, 2023)
Background: This study aimed to investigate the factors affecting the empowerment of faculty members to launch start-ups in the branches of the Islamic Azad University of Tehran. Methods: This research was descriptive-analytical. Its statistical population included 27,000 faculty members working in the Islamic Azad University, Tehran branch. The sampling method was cluster random sampling. The sample size was 50 people in the qualitative part and 384 people in the quantitative part. The research tools were researcher-made questionnaires, with a Likert scale and semi-structured interviews. For statistical analysis, confirmatory factor analysis tests, t-tests, and multivariate regression were used by SPSS software version 23. Results: The results showed that there is a significant difference in the components affecting empowerment, including marketing and commercialization of knowledge (β=0.354), attracting elites and from business (β=0.306), and knowledge sharing (β=0.265). financial risk analysis (β=0.143), formation of business support association (β=0.111), value design and use of new technologies (β=0.075), financial and legal support of the government (β=0.066), creating environmental changes (β=0.056), increasing value-creating activities (β=0.044), providing infrastructure (β=0.037), and discussing startups (β=0.024) in the order of priority. The partial regression showed the impact of discussion about startups and environmental changes on the empowerment of faculty members. Conclusion: It is essential to consider human resources, knowledge commercialization, elite recruitment, knowledge sharing, financial risk analysis, financial and business support, use of new technologies, environmental change, value creation activities, providing infrastructure, about start-ups based on the transformational attitude of management.